Socialization Of Community Knowledge Management About Pharmaceutical Products In Suka Damai Village, Langkat, North Sumatra - Rasyid Syamsuri, Abd.; Anisa, Siti; Tri Utami, Indah; Fablo Purba, Juvantri (CV. Inara, 2023)
Socialization of public knowledge management about pharmaceutical products aims to provide information as a form of dissemination in the form of education. This community service was carried out in Suka Damai Village, Langkat district, North Sumatra Province. The purpose of this community service is to provide and practice knowledge about pharmaceutical products through traditional medicines which are mixed from plant ingredients, animal ingredients, mineral ingredients, galenic preparations, or mixtures of these materials. Traditional medicine can be made into a simple product that can be made and practiced by yourself, for example roll on aromatherapy or commonly called freshcare which has many uses in everyday life. Apart from that, other products such as dry instant ginger drinks can also be consumed with various benefits.The use of natural materials can also be used as a way to open business opportunities. Thus, people gain knowledge and know how to make one of the health products that so far when they want to use it they have to buy it first.